2019
DOI: 10.1158/1538-7445.sabcs18-ot1-10-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT1-10-01: DETECT III/IV study trial – The multicenter study program in patients with HER2-negative metastatic breast cancer and circulating tumor cells

Abstract: Background: The collaborative DETECT study program represents one of the largest study program on metastatic breast cancer worldwide. The main objective of the DETECT trial is to evaluate the efficacy of individualized breast cancer treatment based on the presence and phenotype setting of circulating tumor cells (CTCs). Thus, the DETECT study program is one of the first clinical trial translating the role of CTC enumeration/phenotyping directly into treatment intervention within different breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Interestingly, in the CirCe T-DM1 trial, patients with at least 1 HER2-amplified CTC per 7.5 mL had a low HER2-amplified/HER2-negative ratio, suggesting that these HER2-amplified cells reflect a minor subclone, which may explain the lack of efficacy of anti-HER2 therapy. The results of the DETECT III trial [114], which randomizes patients with HER2-negative metastatic BC and detectable HER2-positive CTC to standard treatment or to standard treatment in combination with lapatinib, are therefore eagerly awaited. In this phase III multicenter trial, HER2-positive CTCs were identified by IHC or FISH after the detection of CTCs by CellSearch Ò .…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in the CirCe T-DM1 trial, patients with at least 1 HER2-amplified CTC per 7.5 mL had a low HER2-amplified/HER2-negative ratio, suggesting that these HER2-amplified cells reflect a minor subclone, which may explain the lack of efficacy of anti-HER2 therapy. The results of the DETECT III trial [114], which randomizes patients with HER2-negative metastatic BC and detectable HER2-positive CTC to standard treatment or to standard treatment in combination with lapatinib, are therefore eagerly awaited. In this phase III multicenter trial, HER2-positive CTCs were identified by IHC or FISH after the detection of CTCs by CellSearch Ò .…”
Section: Breast Cancermentioning
confidence: 99%
“…The primary endpoint of the trial is the CTC clearance rate, which may provide interesting insights into the activity of anti-HER2 agents in these patients. Patients with HER2-negative CTCs may be eligible for inclusion in other studies of the DETECT program: patients with hormone receptor-positive BC and an indication for endocrine therapy receive everolimus or ribociclib in combination with endocrine therapy [114] in the DETECT IVa study, whereas those with an indication for chemotherapy or hormone receptor-negative BC receive eribulin (DETECT IVb). The DETECT program also includes a large number of translational studies [115]: for instance, in DETECT III, HER2-positive CTCs will be analyzed for the presence of PIK3CA mutations.…”
Section: Breast Cancermentioning
confidence: 99%
“…The primary endpoint is CTC clearance, and the secondary endpoints are PFS, overall, all response rate, and dynamic of CTCs. 111 DETECT IV (NCT02035813) is a phase II trial with cohort A having HRpositive MBC patients treated with endocrine therapy combined with everolimus or ribociclib, and with cohort B having triple negative or higher risk HR-positive MBC patients treated with mitotic inhibitor eribulin. The primary endpoints are CTC clearance rate in cohort A and PFS in cohort B.…”
Section: Her2 Discordancementioning
confidence: 99%
“…Indeed, it has been proven that, during treatment, ER+ MBCs can develop ER-CTCs; it has been hypothesized that this phenomenon may reflect the acquisition of therapy resistance by the primary tumor [98]. An interventional trial is currently testing the possibility of using the HER2 status of CTCs to stratify MBC patients [99]. Moreover, CTC expression of protein death-1 ligand correlates with MBC OS, suggesting that CTC evaluation may be useful to predict the sensitivity to specific immunotherapies [100].…”
Section: Clinical Application Of Liquid Biopsy Breast Cancermentioning
confidence: 99%